2012
DOI: 10.4028/www.scientific.net/amr.482-484.1431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Novel Low-Voltage Alternating Current Pulse on Solidification Structure of Al-7Si-0.52Mg Alloy

Abstract: The solidification structure applying a novel low-voltage alternating current pulse (ACP) during solidification of Al-7Si-0.52Mg alloy has been investigated. The results indicated that the grain density increased with increasing current density. A remarkable refinement of grain occurred, and the microstructure of primary α-Al phase transforms from developed dendrites to fine rosette equiaxed grain when the current density was more than 230 Acm-2. The grain refinement was mainly achieved during the nucleation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In general, the effect of ECP treatment during the nucleation stage includes the change in the nucleation activity energy, Joule heating and ∆G e . As was indicated in previous studies [29], the role of the change in the nucleation activity energy to the nucleation rate was obviously insignificant in the Al-7Si alloy under AECP with 990 A, and thus the corresponding contribution is not expected to be significant under the lower AECP. In addition, the contribution of Joule heating is also not expected to be prominent for the present current density being no more than 67 A•cm −2 since Joule heating is almost negligible for the current density of~120 A•cm −2 in the Al-7Si alloy [20].…”
Section: Resultssupporting
confidence: 52%
“…In general, the effect of ECP treatment during the nucleation stage includes the change in the nucleation activity energy, Joule heating and ∆G e . As was indicated in previous studies [29], the role of the change in the nucleation activity energy to the nucleation rate was obviously insignificant in the Al-7Si alloy under AECP with 990 A, and thus the corresponding contribution is not expected to be significant under the lower AECP. In addition, the contribution of Joule heating is also not expected to be prominent for the present current density being no more than 67 A•cm −2 since Joule heating is almost negligible for the current density of~120 A•cm −2 in the Al-7Si alloy [20].…”
Section: Resultssupporting
confidence: 52%
“…Then the corresponding homogeneous distribution of electric current is modified because crystal nuclei have different electrical resistivity from that of the aluminum melt. Note that various distributions of electric current corresponds to the different G e , and thus Δ G e is given as [28,29,38]:ΔGe=μ8sans-serifπtrue70%∬bold-italicj1(r)bold-italicj1(bold-italicr)bold-italicj2(r)bold-italicj2(bold-italicr)|rbold-italicr|d3rd3bold-italicr, where r and r ′ are two different positions in space, j is the current density and μ is the magnetic permeability. The subscript 1 and 2 represent the states before and after the formation of crystal nuclei.…”
Section: Resultsmentioning
confidence: 99%
“…Since the solidification of pure metal is simple due to non-existent solute transport and knowledge about how electropulsing affects the solidification of pure aluminum has been accumulated by experimental and theoretical analysis, pure aluminum is selected to ensure that the formation mechanism of FEG is better clarified during the solidification process. For the work, the alternating electropulsing with frequency of 50 Hz and the effective value of current amplitude of less than 990 A was applied, since the prior work [20,29] indicated that effect of Joule heating and forced convection induced by Lorentz force on grain refinement could be distinguished by experiments with the mold embedded the wire mesh when electropulsing with 990 A was applied. It made it possible to reveal the role of Δ G e on the formation of FEG based on the differences in electrical resistivities between the solid crystal nuclei and the liquid matrix.…”
Section: Introductionmentioning
confidence: 99%